Excellent electronic transport in heterostructures of graphene and monoisotopic boron-nitride grown at atmospheric pressure. (16th June 2020) - Sonntag, J; Li, J; Plaud, A; Loiseau, A; Barjon, J; Edgar, J H; Stampfer, C
Abstract: Hexagonal boron nitride (BN), one of the very few layered insulators, plays a crucial role in 2D materials research. In particular, BN grown with a high pressure technique has proven to be an excellent substrate material for graphene and related 2D materials, but at the same time very hard to replace. Here we report on a method of growth at atmospheric pressure as a true alternative for producing BN for high quality graphene/BN heterostructures. The process is not only more scalable, but also allows to grow isotopically purified BN crystals. We employ Raman spectroscopy, cathodoluminescence, and electronic transport measurements to show the high-quality of such monoisotopic BN and its potential for graphene-based heterostructures. The excellent electronic performance of our heterostructures is demonstrated by well developed fractional quantum Hall states, ballistic transport over distances around 10  µ m at low temperatures and electron-phonon scattering limited transport at room temperature.